Two-layer electrified pressure-driven flow in topographically structured channels - Dubrovina,E; Craster,RV; Papageorgiou,DT (Journal of Fluid Mechanics, 2017)
The flow of two stratified viscous immiscible perfect dielectric fluids in a channel withtopographically structured walls is investigated. The flow is driven by a streamwisepressure gradient and an electric field across the channel gap. This problem isexplored in detail by deriving and studying a nonlinear evolution equation for theinterface valid for large-amplitude long waves in the Stokes flow regime. For flatwalls, the electrified flow is long-wave unstable with a critical cutoff wavenumberthat increases linearly with the magnitude of the applied voltage. In the nonlinearregime, it is found that the presence of pressure-driven flow prevents electrostaticallyinduced interface touchdown that has been observed previously – time-modulatednonlinear travelling waves emerge instead. When topography is present, linearly stableuniform flows become non-uniform spatially periodic steady states; a small-amplitudeasymptotic theory is carried out and compared with computations. In the linearlyunstable regime, intricate nonlinear structures emerge that depend, among otherthings, on the magnitude of the wall corrugations. For a low-amplitude sinusoidalboundary, time-modulated travelling waves are observed that are similar to thosefound for flat walls but are influenced by the geometry of the wall and slide over itwithout touching. The flow over a high-amplitude sinusoidal pattern is also examinedin detail and it is found that for sufficiently large voltages the interface evolves tolarge-amplitude waves that span the channel and are subharmonic relative to the wall.A type of ‘walking’ motion emerges that causes the lower fluid to wash through thetroughs and create strong vortices over the peaks of the lower boundary. Non-uniformsteady states induced by the topography are calculated numerically for moderate andlarge values of the flow rate, and their stability is analysed using Floquet theory.The effect of large flow rates is also considered asymptotically to fi